INFLUENCE OF INCENTIVES ON PERFORMANCE OF MAN BATAM EMPLOYEES - Arib Muhammady; Adi Irawan Setiyanto (Pusat P2M Politeknik Negeri Batam, 2022)
Abstract. Institutions are one of the parties that cannot avoid various demands for changes and developments in the era of the industrial revolution 4.0. In dealing with these changes, institutions need a reliable and professional human resource (HR) in their fields. Therefore, an Institution needs to improve the quality of employees who work in it, because employees are one of the main and very important components of an institution or organization. Employee performance is one of the determining factors for the success of an institution or organization in achieving its goals. One way that can be taken to improve employee performance is by providing remuneration (incentives) to employees. This study aims to determine how the effect of incentives on employee performance MAN BATAM. This research is a quantitative descriptive study with the research sample being 88 employees of MAN BATAM. Data were obtained through questionnaires and interviews. The instrument used to collect data is a questionnaire that has been declared valid and reliable based on the results of the instrument trial. The research data were analyzed by simple linear regression analysis and partial significance test T (T-test) and processed with the SPSS 21 program. The results showed that incentives significantly affected the performance of MAN BATAM employees. Keywords: Industrial Revolution 4.0, Institution, Employee Performance, Incentive